EFEKTIVITAS MEDIA GAME ULAR TANGGA BERBASIS CANVA PADA MATERI PECAHAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Nur Lia Slamet Hidayah; Dian Kusmaharti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of using Canva-based snakes and ladders game media in improving the learning outcomes of fourth-grade elementary school students on the topic of fractions. This research was conducted because of low student learning outcomes, caused by a lack of diverse and interactive learning media. This situation makes students feel uninterested and struggle to understand concepts that feel difficult. Data collection techniques included observations, questionnaires, and tests. This study employs a descriptive approach with a one-group pretest-posttest experimental design, involving 28 participants. The digital snakes and ladders game serves as an engaging and interactive tool that helps enhance students' understanding. The results of the study indicate that the average learning outcome scores increased from the pre-test to the post-test. The data analysis process utilized the N-Gain test. Therefore, it can be concluded that using Canva-based snakes and ladders game media is highly effective, clear, and makes learning enjoyable, making it a viable alternative in learning media to improve students' mathematics learning outcomes.